COMMUNITY EMPOWERMENT THROUGH ORGANIC RICE CULTIVATION: CREATING A SUSTAINABLE AGRICULTURAL ENVIRONMENT - Rezza, Muhammad; Simatupang, Erwinton (Transpublika Publisher, 2023)
The PSRLB Program in Talang Ubi Utara Village represents a commendable initiative aimed at promoting sustainable and environmentally friendly agriculture practices. This program actively engages local farmers and the community in the pursuit of organic rice cultivation. It achieves this by providing farmers with essential training and guidance in adopting the Sustainable System of Rice Intensification (SRI) method, a sustainable approach that eliminates the need for chemical fertilizers. The results of the PSRLB program's implementation have been promising. It has not only significantly increased the productivity and quality of organic rice harvests but has also mitigated negative environmental impacts associated with conventional farming practices. As such, the PSRLB program stands as a shining example, offering inspiration to other farming communities seeking to embrace sustainable and eco-friendly agricultural methods. Its success underscores the potential for agriculture to harmoniously coexist with nature while fostering healthier, more prosperous farming communities.